Extraction, structure and pharmacological effects of the polysaccharides from Cordyceps sinensis: A review. (February 2022) - Yuan, Qianghua; Xie, Fan; Tan, Jing; Yuan, Yan; Mei, Hu; Zheng, Yan; Sheng, Rong
Graphical abstract: Highlights: Hot water extraction is the most common extraction method. Monosaccharide composition, molecular weight and configuration may be the key to affecting biological activity. C. sinensis polysaccharides are expected to treat diabetes, cancer, atherosclerosis, and intestinal, liver and kidney injury. Carrying out clinical research is an important research direction in the future. Abstract: Cordyceps sinensis (the new species name is Ophiocordyceps sinensis ) is a precious Chinese medicinal material. The polysaccharides are one of the important biologically active components of C. sinensis and have attracted more and more attention from scholars. The purpose of the review is to systematically review relevant studies on the extraction, structure, and pharmacological effects of C. sinensis polysaccharides to support their further application as therapeutic agents and functional foods. The results show that these C. sinensis polysaccharides have different structure, which may be closely related to their pharmacological activities. C. sinensis polysaccharides have various pharmacological effects including anti-oxidant, anti-inflammatory, immunomodulatory and prebiotics effect. Moreover, C. sinensis polysaccharides can produce anti-cancer, anti-diabetes and anti-atherosclerosis effects, and have protective effects on the liver, intestine and kidney. In short, C. sinensis polysaccharides show potential medicinal value, and are expected to be used in the treatment of many diseases.